Eo-Alpine metamorphism and the ‘mid-Miocene thermal event’ in the Western Carpathians (Slovakia): New evidence from multiple thermochronology - Danisik, M.; Kohut, M.; Evans, Noreen; McDonald, Bradley (Cambridge University Press, 2012)
A combination of zircon (U–Th)/He (ZHe), apatite fission track (AFT) and apatite (U–Th)/He (AHe) dating methods is applied to constrain the metamorphic and exhumation history of the Tatric part of the Branisko Mountains in the Western Carpathians. ZHe ages from the basement samples prove the basement experienced a very low-grade to low-grade Eo-Alpine metamorphic overprint in mid-Cretaceous times. Miocene AFT and AHe ages found in the basement and in the Palaeogene sediments conclusively demonstrate that the Branisko Mts experienced a ‘mid-Miocene thermal event’. This thermal event had a regional character and was related to magmatic and/or burial heating that exposed the sediment and basement samples to ~ 120–130°C and ~ 100–190°C, respectively.